Evaluasi Implementasi Hasil Diklat Teknis Guru IPA Madrasah Tsanawiyah - Umul Hidayati (Badan Litbang dan Diklat Kementerian Agama RI, 2020)
AbstractThe research entitled Implementation Evaluation of the Results of the 2019 Tsanawiyah Madrasah Teacher Training was conducted in 10 BDK regions. The results showed that after the training, teachers experienced a very high increase in competence, obtaining scores above 80. Generally, science teachers, alumni of education, and training felt that after attending the training, there is an increase in incompetence in terms of knowledge, skills, and attitudes. Among the three competency supporting variables, the attitude variable has the highest contribution, followed by the knowledge and skills variables. The increase in the high competence of science teachers after attending this training was observed by their ability to implement them in learning. However, the results of this training have not had a significant impact on improving the quality of madrasas, because, in most madrasas, the results of training are still challenging to implement due to many factors, including unavailability of laboratory facilities, the uneven ability of science teachers both in learning and in utilization. science equipment, the number of science teachers who have received training is still very few, and madrasah policies that do not support science learning.Â AbstrakPenelitian berjudul Evaluasi Implementasi Hasil Diklat Teknis Guru Madrasah TsanawiyahTahun 2019 yang dilakukan di 10 wilayah BDK, hasilnya menunjukkan bahwa pasca diklat guru mengalami peningkatan kompetensi sangat tinggi, dengan memperoleh skor di atas 80. Umumnya para guru IPA alumni diklat merasakan bahwa setelah mengikuti diklat, ada peningkatan kompetensi baik dari sisi pengetahuan, keterampilan dan sikap. Diantara ketiga variabel pendukung kompetensi tersebut, variabel sikap mempunyai kontribusi tertinggi, disusul variabel pengetahuan dan keterampilan. Peningkatan kompetensi guru IPA yang tinggi setelah mengikuti diklat ini sebenarnya juga diikuti oleh kemampuannya mengimplementasikan dalam pembelajaran. Namun demikian, hasil diklat ini belum berdampak signifikan dalam meningkatkan mutu madrasah, karena pada sebagian besar madrasah, hasil diklat masih sulit diimplementasikan karena terkendala banyak faktor antara lain: sarana laboratorium yang belum tersedia, kemampuan guru IPA yang belum merata baik dalam pembelajaran maupun dalam pemanfaatan peralatan IPA, jumlah guru IPA yang pernah memperoleh diklat masih sangatÂ Â